It’s a TRIM-endous view from the top: the varied roles of TRIpartite Motif proteins in brain development and disease - Dudley-Fraser, Jane; Rittinger, Katrin (Frontiers in Molecular Neuroscience, 2023)
The tripartite motif (TRIM) protein family members have been implicated in a multitude of physiologies and pathologies in different tissues. With diverse functions in cellular processes including regulation of signalling pathways, protein degradation, and transcriptional control, the impact of TRIM dysregulation can be multifaceted and complex. Here, we focus on the cellular and molecular roles of TRIMs identified in the brain in the context of a selection of pathologies including cancer and neurodegeneration (Figure 1). By examining each disease in parallel with described roles in brain development, we aim to highlight fundamental common mechanisms employed by TRIM proteins and identify opportunities for therapeutic intervention.